An analysis on the revoking mechanisms for JSON Web Tokens - László Viktor Jánoky; János Levendovszky; Péter Ekler (International Journal of Distributed Sensor Networks)
JSON Web Tokens provide a scalable solution with significant performance benefits for user access control in decentralized, large-scale distributed systems. Such examples would entail cloud-based, micro-services styled systems or typical Internet of Things solutions. One of the obstacles still preventing the wide-spread use of JSON Web Token–based access control is the problem of invalidating the issued tokens upon clients leaving the system. Token invalidation presently takes a considerable processing overhead or a drastically increased architectural complexity. Solving this problem without losing the main benefits of JSON Web Tokens still remains an open challenge which will be addressed in the article. We are going to propose some solutions to implement low-complexity token revocations and compare their characteristics in different environments with the traditional solutions. The proposed solutions have the benefit of preserving the advantages of JSON Web Tokens, while also adhering to stronger security constraints and possessing a finely tuneable performance cost.